Optimization of Acetic Acid Production Process Using the Cativa Method for Increasing Product Purity - Salma, Aliya Farrasty; Ramadhan, Gilang; Maharani, Nina Yunita; Fatimah, Rachel Salwa (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Acetic acid finds extensive application in the food, chemical, pharmaceutical, polymer, paint, and textile industries. Considering these applications, acetic acid production needs to be optimized for high efficiencies in both energy and mass in order to maximize profit. In this work, we will be explaining how one could maximize the yield of acetic acid and show results on purity analysis. By modifying the process, the previous reactor was replaced, and the separation unit was removed. Whereas case study tools in Aspen HYSYS V12 were used in order to carry out the purity analysis of the current modified process. According to these process modifications, the acetic acid yield increased from 85.00% to 100% purity. The results of the case study of acetic acid production indicate that the higher the mole fraction ratio of acetic acid to the total product mole fraction, the higher the purity of the liquid product produced from the reactor. Conversely, if the mole fraction ratio of acetic acid to the total product mole fraction decreases, the purity of the liquid product will be reduced, which means that an increase in the mole fraction of by-products or contaminants occurred in the mixture. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).